Mr. Wolf's class - Steinke, Aron Nels (New York : Graphix, 2018)
Mr. Wolf has just started teaching at Hazelwood Elementary. He wants the first day of school to go well, but he's got his hands full with his new class. Some of his students include: Margot, who is new in town and is trying to make friends. Sampson, who brought something special to school for show-and-tell. Aziza, who just wants everyone to be quiet and do their work. And Penny, who is very sleepy because she has a new baby brother at home, goes missing!
School Library Journal, May 2018
Publishers Weekly, April 2018
Kirkus Starred, March 2018
Booklist, May 2018
New York Times, August 2018
Horn Book, November 2018
Keywords: Elementary school teachers -- Comic books, strips, etc. -- Fiction; Schools -- Comic books, strips, etc. -- Fiction; First day of school -- Comic books, strips, etc. -- Fiction; Friendship -- Comic books, strips, etc. -- Fiction; Elementary school teachers -- Juvenile fiction; Schools -- Juvenile fiction; First day of school -- Juvenile fiction; Friendship -- Juvenile fiction; Humorous comics; Graphic novels; Graphic novels; Comics (Graphic works)